Turning around ‘stuck’ schools in England: effective leadership in extremely challenging circumstances - Munoz Chereau, Bernardita; Ehren, Melanie (Perspectiva Educacional, 2024)
This paper presents a two-year qualitative multi-site case study in six English state-funded schools (thee primary and three secondary). These schools were identified by Ofsted as ‘stuck’ after failing their inspections for more than a decade but managed to turnaround their overall inspection effectiveness, despite the wider contextual challenges. Drawing from an analysis of 50 documents, 22 interviews and focus groups with school leaders, we detail the schools’ trajectories and leadership practices that allowed leaders to improve schools’ overall effectiveness. Staff from ‘un-stuck’ schools described a combination of 1) distributed leadership, 2) moral purpose, 3) stabilising teams, 4) external support, 5) building trust, 6) positive relationships with parents and the community, 7) vision of high expectations, 8) systematic approach to improve behaviour, and 9) strong internal governance and accountability that allowed their significant improvement. These characteristics contribute to our understanding of effective turnaround leadership of schools working in disadvantaged contexts.